2023
DOI: 10.3389/fenvs.2023.1126275
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary game and simulation analysis on quality supervision of low-carbon renovation of high-carbon emission enterprises under the reward and punishment mechanism

Abstract: From the perspective of multi-stakeholders, considering the rent-seeking phenomenon existing in the inspection and acceptance of low-carbon renovation under the government’s reward and punishment mechanism, this paper constructs a tripartite evolutionary game model of the government, third-party testing institutions, and high-carbon emission enterprises, analyzes the stability of the evolutionary strategies of all parties involved, and tests the influence of the reward and punishment mechanism, rent-seeking co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The power grid companies are driven by profit-seeking objectives to maximize their own economic profits. However, the resulting unsustainable behaviors have caused environmental pollution, high carbon emissions and many other problems, which not only increase the input costs, but also damage the brand value of the power grid companies [31]. The government plays in a leading role in the sustainable development of PCPs, aiming to take into account the economic benefits brought about by the development of PCPs while at the same time taking into account the environmental and social benefits.…”
Section: Critical Stakeholders In the Sustainable Development Of Pcpsmentioning
confidence: 99%
“…The power grid companies are driven by profit-seeking objectives to maximize their own economic profits. However, the resulting unsustainable behaviors have caused environmental pollution, high carbon emissions and many other problems, which not only increase the input costs, but also damage the brand value of the power grid companies [31]. The government plays in a leading role in the sustainable development of PCPs, aiming to take into account the economic benefits brought about by the development of PCPs while at the same time taking into account the environmental and social benefits.…”
Section: Critical Stakeholders In the Sustainable Development Of Pcpsmentioning
confidence: 99%
“…Owing to uneven carbon emissions across provinces, green transfer payment projects can be used to build green projects and achieve energy conservation and emission reduction [28]. From an industrial perspective, formulating differentiated subsidy programs [29], improving reward and punishment mechanisms [30], and establishing governance mechanisms shared by stakeholders [31] can promote the green transformation of various industries and achieve carbon emission reduction policy goals. The literature above shows that the stakeholders in the government's administrative emission reduction are mainly the manufacturing industry, which emits carbon emissions, while ignoring a basic variable in social and economic activities-citizens [32].…”
Section: Carbon Reduction Policy Researchmentioning
confidence: 99%
“…In addition, some scholars have discussed the relationship between public participation in environmental governance and the monitoring of corporate environmental violations in China (Zhang et al, 2023). By constructing a model involving local governments, third-party testing institutions, and high carbon emission enterprises, Weng et al (2023) studied the rent-seeking phenomenon that enterprises face in low-carbon environments. Based on the tripartite relationship between local governments, enterprises, and the public, Cao (2021) demonstrated that the public has a certain degree of political influence in supervising environmental governance and can to some extent replace aspects of the government's responsibilities.…”
Section: Related Literaturementioning
confidence: 99%